2021
DOI: 10.1111/twec.13077
|View full text |Cite
|
Sign up to set email alerts
|

Political stability and fiscal consolidation in sub‐Saharan African countries

Abstract: Fiscal policy decision‐making in sub‐Saharan African countries has not always been understood, and the existing literature has generally emphasised the role of macroeconomic factors to justify government fiscal performances. This study highlights the essential role of political stability in the fiscal consolidation decision‐making process in sub‐Saharan African countries. We perform a panel logit model for twenty‐seven (27) sub‐Saharan African countries for the period 2000–15. We show that government stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Hence, there might be other factors at play that may be responsible for observed shift, not necessarily the institutional improvement. In line with the literature, these factors may include public debt, terms of trade volatility, polarisation of preferences (Priewe, 2020;Yabré & Semedo, 2021;Jaillet & Pfister, 2022), or even levels of corruption (Bausch, 2019).…”
Section: Resultsmentioning
confidence: 83%
“…Hence, there might be other factors at play that may be responsible for observed shift, not necessarily the institutional improvement. In line with the literature, these factors may include public debt, terms of trade volatility, polarisation of preferences (Priewe, 2020;Yabré & Semedo, 2021;Jaillet & Pfister, 2022), or even levels of corruption (Bausch, 2019).…”
Section: Resultsmentioning
confidence: 83%
“…Following the paper by Giavazzi -Pagano (1990), the empirical literature on the response of real GDP and private demand to contractionary fiscal policy falls within two strands-expansionary austerity (non-Keynesian effects of fiscal policy) (Giavazzi -Pagano, 1990, 1996Alesina -Perotti, 1997;Alesina -Ardagna, 1998;Perotti, 1999;Ardagna, 2004;von Hagen -Strauch, 2001;van Aarle -Garretsen, 2003;Giudice et al, 2007;Alesina et al, 2015;Jordà -Taylor, 2016;Alesina et al, 2019;Afonso -Leal, 2020; and contractionary austerity (Hjelm, 2002b;van Aarle -Garretsen, 2003;Schclarek, 2007;Guajardo et al, 2014;Arizala et al, 2021;Yabré -Semedo, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, this approach is simple and transparent in its application. However, regarding the discrepancies in unemployment data, several authors have suggested that for developing countries, the real GDP growth rate instead of the unemployment rate should be used (Brunila et al, 1999;Fatás -Mihov, 2003;Alberola -Sousa, 2017;Yabré -Semedo, 2021). We follow the same procedure to formulate the BFI.…”
Section: Bfimentioning
confidence: 99%
See 2 more Smart Citations